Ijtihad Ali Ibn Abi Thalib Bidang Jinayah dalam Kitab Muwatha' Imam Malik - Faisal Yahya (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2012)
Abstract. Ali made the decision diyat in Yemen, but not accepted by the tribes in Yemen, so that they said to the Prophet. This shows that ijtihad Ali was not followed by these tribes. Ali has also been requested by Muawiyah opinion on issues in the region, this shows the depth of the science of Ali. In this paper will be described ijtihad Ali in the book Muwatha' will then be sought about the extent jinayah ijtihad was followed by the priests of his contemporaries and schools. There are two ijtihad Imâm Ali in Muwatha', the first woman who gave birth within six months is not proof that she committed adultery, ijtihad is followed by the schools of his contemporaries and the priests, the second sentence wine drinkers eighty lashes, this opinion is followed by 'Umar ibn Khaththab, the Hanafî and Maliki.